Nilai - Nilai Pendidikan Agama Hindu Dalam Pementasan Barong Ida Ratu Gede Dalem Pada Upacara Nuwur Di Pura Dalem Desa Adat Tangeb Badung - I Gusti Putu Agung Merta Wibawa; I Ketut Sudarsana (Jayapangus Press, 2019)
The ferformance of Barong Ida Ratu Gede Dalem originated from the belief of Tangeb resident toward the manifestation of Ida Sang Hyang Widhi Wasa which is implemented in the form of Barong Ida Ratu Gede Dalem which has magical power. This power can help the villagers in many things. In this believe, nuwur ritual presentation of Barong Ida Ratu Gede Dalem started. When the people of Desa Adat Tangeb face problems which they can’t solve them selves, they will prray to God in his manifestation as Barong Ida Ratu Gede Dalem to get the soluions. When the problem are solved, people thank God through his manifestation as Barong Ida Ratu Gede Dalem by condungting a ritual performance which is called ”nuwur”.